Parasite-derived plasma microparticles contribute significantly to malaria infection-induced inflammation through potent macrophage stimulation. - Kevin N Couper; Tom Barnes; Julius C R Hafalla; Valery Combes; Bernhard Ryffel; Thomas Secher; Georges E Grau; Eleanor M Riley; J Brian de Souza (PLoS Pathogens)
There is considerable debate as to the nature of the primary parasite-derived moieties that activate innate pro-inflammatory responses during malaria infection. Microparticles (MPs), which are produced by numerous cell types following vesiculation of the cellular membrane as a consequence of cell death or immune-activation, exert strong pro-inflammatory activity in other disease states. Here we demonstrate that MPs, derived from the plasma of malaria infected mice, but not naive mice, induce potent activation of macrophages in vitro as measured by CD40 up-regulation and TNF production. In vitro, these MPs induced significantly higher levels of macrophage activation than intact infected red blood cells. Immunofluorescence staining revealed that MPs contained significant amounts of parasite material indicating that they are derived primarily from infected red blood cells rather than platelets or endothelial cells. MP driven macrophage activation was completely abolished in the absence of MyD88 and TLR-4 signalling. Similar levels of immunogenic MPs were produced in WT and in TNF(-/-), IFN-gamma(-/-), IL-12(-/-) and RAG-1(-/-) malaria-infected mice, but were not produced in mice injected with LPS, showing that inflammation is not required for the production of MPs during malaria infection. This study therefore establishes parasitized red blood cell-derived MPs as a major inducer of systemic inflammation during malaria infection, raising important questions about their role in severe disease and in the generation of adaptive immune responses.